International class curriculum development model: a case study in Indonesia and Malaysia universities - Wahidmurni, Wahidmurni; Octaberlina, Like Raskova; Nor, Mohd Roslan Mohd; Nikmah, Faridatun; Hanifah, Nur Hidayah; Ningrum, Dian Eka Aprilia Fitria; Mubarok, Harir; Rabbani, Imdad (International Journal of Evaluation and Research in Education (IJERE), 2024)
Internationalization of the curriculum in holding international classes is an important topic in efforts to internationalize universities. This research aims to investigate the concept of curriculum design, implementation, and review of international class curricula. A qualitative approach with a case study design is applied to examine the best practices of one of the universities in Indonesia and Malaysia included in the Quacquarelli Symonds World University Rankings (QS-WUR) ranking. Data collection is carried out using documentation techniques by searching the university website, observing, and interviewing informants such as: program managers, students, lecturers, and academic support staffs. The research results show that: i) the curriculum design adopts the national curriculum by adding an introduction to local culture and language, as well as developing an international experience program; ii) curriculum implementation is carried out by opening special classes in Indonesia and regular classes in Malaysia, international experience is mandatory in Indonesia and optional in Malaysia; and iii) curriculum reviews are carried out periodically by the study program with support from the internal quality assurance unit involving stakeholders, to be further assessed through national and international accreditation. The research results become an initial reference for universities in the context of campus internationalization by opening international classes through curriculum internationalization.